A Database for Reproducible Computational Research - Gomes, Gabriel F. T.; Borin, Edson (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2012)
The ability to reproduce the experiments of a scientific research is one of the fundamental principles of the scientific method, as failing to reproduce it and obtain results equal (or very similar) to the original might imply that the later were wrong. In compiler and computer architecture research, reproducibility requires a researcher to be able to compile and execute software on (possibly many) computing systems in a repeatable manner. Though the source code for the studied applications, operating systems and compiler tool chains are often available, it is sometimes still impossible to exactly reproduce one experiment due to the lack of information about versioning of the code, build configuration and environmental setup. In this work we propose a database for gathering experimental setup information as well as related experimental results to enforce reproducibility and to enable results sharing among the researchers.